Gene Expression Profiling during Murine Tooth Development - Landin, Maria A d.; Shabestari, Maziar; Babaie, Eshrat; Reseland, Janne E.; Osmundsen, Harald (Frontiers in Genetics, 2012)
The aim of this study was to describe the expression of genes, including ameloblastin (Ambn), amelogenin X chromosome (Amelx) and enamelin (Enam) during early (pre-secretory) tooth development. The expression of these genes has predominantly been studied at post-secretory stages. Deoxyoligonucleotide microarrays were used to study gene expression during development of the murine first molar tooth germ at 24h intervals, starting at the eleventh embryonic day (E11.5) and up to the seventh day after birth (P7). The profile search function of Spotfire software was used to select genes with similar expression profile as the enamel genes (Ambn, Amelx and Enam). Microarray results where validated using real-time Reverse Transcription-Polymerase Chain Reaction (real-time RT-PCR), and translated proteins identified by Western blotting. In situ localisation of the Ambn, Amelx and Enam mRNAs were monitored from E12.5 to E17.5 using deoxyoligonucleotide probes. Bioinformatics analysis was used to associate biological functions with differentially (p ≤0.05) expressed (DE) genes. Microarray results showed a total of 4362 genes including Ambn, Amelx and Enam to be significant differentially expressed throughout the time-course. The expression of the three enamel genes was low at pre-natal stages (E11.5-P0) increasing after birth (P1-P7). Profile search lead to isolation of 87 genes with significantly similar expression to the three enamel proteins. The mRNAs expressed in dental epithelium and epithelium derived cells. Although expression of Ambn, Amelx and Enam were lower during early tooth development compared to secretory stages enamel proteins were detectable by Western blotting. Bioinformatic analysis associated the 87 genes with multiple biological functions. Around thirty-five genes were associated with fifteen transcription factors.